Pelvic Pain Disorders and Associated Acceptability of Office Hysteroscopy [A288]. (May 2022) - Brant, Amanda C.; Echetebu, Nneanata; Mara, Kristin; Laughlin-Tommaso, Shannon; Hopkins, M.; Green, Isabel
Abstract : INTRODUCTION: Despite the benefits, convenience, and acceptability of office hysteroscopy (OH), 20% of patients find OH unacceptable. In this study we defined acceptability as willingness to undergo office hysteroscopy in the future and investigated whether patients with co-existing pelvic pain disorders were more likely to find OH unacceptable. METHODS: Patients who underwent OH from 12/2016 to 6/2018 were included. Patients were asked to rate acceptability at the time of their procedure. Retrospective chart review was used to identify patients with pelvic pain disorders defined as chronic pelvic pain (CPP), dysmenorrhea, vulvodynia, dyspareunia, or high tone pelvic floor dysfunction (PFD). Patients rating OH as acceptable (Likert scale 4–5) were compared to those rating it as unacceptable (Likert scale 1–2). Comparisons between groups were made using a t-test or Wilcoxon rank sum test for continuous data, and a Chi-square test for categorical data. This study was determined to be exempt from the requirement for IRB approval (IRB #20–009387). RESULTS: Compared to patients in the "acceptable" group (n=929), patients who rated OH as "unacceptable" (n=55) reported higher during and post-procedure pain scores and lower satisfaction rates ( P <.001). Prior diagnosis of PFD ( P <.001) and dyspareunia ( P =.003) were both associated with finding OH unacceptable. Dysmenorrhea, CPP, and vulvodynia were associated with unacceptability but did not achieve significance. CONCLUSION: A preexisting diagnosis of a pelvic pain disorder, specifically PFD and dyspareunia, was associated with unacceptability of OH. Implementing triage criteria for patients to pursue hysteroscopy with sedation or anesthesia could help improve patient satisfaction and warrants additional study.